2018
DOI: 10.1002/esp.4364
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the sediment deposition behind check‐dams under different soil erosion conditions on the Loess Plateau, China

Abstract: To maintain a reasonable sediment regulation system in the middle reaches of the Yellow River, it is critical to determine the variation in sediment deposition behind check‐dams for different soil erosion conditions. Sediment samples were collected by using a drilling machine in the Fangta watershed of the loess hilly–gully region and the Manhonggou watershed of the weathered sandstone hilly–gully (pisha) region. On the basis of the check‐dam capacity curves, the soil bulk densities and the couplet thickness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…The results were in general agreement with other reported ASSY for the CLP. For example, the mean ASSY was found to be 0.31 × 10 4 t/(km 2 a) during 1975–2013 within the Fangta catchment of the Yanhe watershed near the plateau–gully region (Wei et al, 2018), while a higher mean ASSY of 1.20 × 10 4 t/(km 2 a) was reported for the Nianyegou catchment of the Wudinghe watershed in the northern hilly–gully region during A.D. 1960–1990 (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were in general agreement with other reported ASSY for the CLP. For example, the mean ASSY was found to be 0.31 × 10 4 t/(km 2 a) during 1975–2013 within the Fangta catchment of the Yanhe watershed near the plateau–gully region (Wei et al, 2018), while a higher mean ASSY of 1.20 × 10 4 t/(km 2 a) was reported for the Nianyegou catchment of the Wudinghe watershed in the northern hilly–gully region during A.D. 1960–1990 (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The couplet specific sediment yield (CSSY) and annual specific sediment yield (ASSY) were calculated based on the methods of Wang et al (2019) and Wei et al (2018), which were the common ways to estimate the sediment yield within the check dams and landslide‐dammed reservoirs on the CLP. Briefly, the CSSY and ASSY in the JB and HS catchments during A.D. 1850–2000 were determined from Equations and , respectively: CSSYgoodbreak=italicδ·H·()S1goodbreak+S2goodbreak+S1·S23·italicTE·A ASSYgoodbreak=i=1nCSSY where S 1 and S 2 are the top and bottom surface areas of each couplet (m 2 ), respectively; H is the thickness of each couplet (m); δ is the bulk density (1.4 t/m 3 as the mean density of representative sediment samples from check dams and landslide‐dammed reservoirs on the CLP; Zhang et al, 2009); A is the catchment area of the reservoir (m 2 ); TE is the trapping efficiency of the landslide dam (assuming 100% TE due to intact dams since the formation of both reservoirs); n is the number of the couplet within an individual year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area shows a landscape of high-density and deep-cut gullies with a gully density of 3.8 km/km 2 [50], and consequently an extremely broken and undulating topography. Three main gully types exist on the Chinese Loess Plateau: hillslope gully, valley floor gully and valley bank gully [19] (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Yu et al suggested that climate change, especially precipitation, has a strong influence on soil erosion in the Loess Plateau [28]. Wei et al analyzed a small watershed in the Loess Plateau and considered the Grain for Green Project to be the main reason for the decrease in the soil erosion in the Fangta watershed [29]. Although scholars have studied the effects of various factors, including climate, terrain, soil, and vegetation, on soil erosion [30][31][32], few have discussed their different effects on soil erosion depending on the land use type.…”
Section: Introductionmentioning
confidence: 99%